Thermo-chemical water splitting: Selection of priority reversible redox reactions by multi-attribute decision making. (June 2021) - Deng, Yimin; Dewil, Raf; Appels, Lise; Li, Shuo; Baeyens, Jan; Degrève, Jan; Wang, Guirong
Abstract: Hydrogen is a top chemical and potential fuel. Its sustainable production from biomass or water splitting gains importance. Whereas sole thermal water splitting requires too high temperatures, thermo-chemical water splitting cycles offer a solution at moderate temperatures. Such cycles were investigated over the past decades, mostly by small-scale experiments and mainly to prove their concept without judgment of their practical, economic, environmental and cyclic performance. To facilitate the decision making and to guide future priority research, these multiple aspects can be combined in a global screening system that applies the improved Analytic Hierarchy Process (AHP) and grey relational TOPSIS, together with the use of linear and non-linear combination weighing. The assessment is quantitative and comprehensive, emphasizing the complex relationship between energy efficiency, conversion, recyclability, economy and environmental quality. The total index combines systematics and flexibility through its multi-objective and multi-level nature. The index helps users, system manufacturers, researchers and governments to select the most appropriate future schemes. Very high temperature reactions of e.g. metal-metal oxides, metal-metal hydroxides, perovskites or doped ceria were not included. At the required temperatures, concentrated solar energy is the evident heat source, although applicable temperatures should meet the mechanical and thermal constraints of the solar receiver-reactor construction materials. The experimental set-up that will be used for subsequent pilot-scale solar testing is briefly described. As a result of the multi-attribute assessment, 4 out of 24 oxidation/reduction reactions are selected for further laboratory or preferably pilot-scale application, including the MnFe2 O4, MnO/NaMnO2 and ZnO/Fe3 O4 /ZnFe2 O4 redox reactions. Graphical abstract: Image 1 Highlights: Water splitting can produce hydrogen at moderate temperatures by oxidation/reduction cycles. Literature cites numerous halide, iron oxide, sulfur and metal or alkali metal processes. Low temperature cycles are assessed by multi-attribute ranking using quantified parameters. By this objective ranking, 4 out of 24 redox cycles are selected for further pilot-scale development. MnFe2 O4, MnO/NaMnO2 and ZnO/Fe3 O4 /ZnFe2 O4 merit priority investigation.